Does popularity compensate for expertise in blog advertorials? - Clara, New Beishi (2013)
This study investigates how popularity and product expertise of a blogger can influence the readers’ attitudes towards the blog advertorial, attitude towards product advertised and the eventual purchase intention of the products. We set out to examine how popularity and expertise differ in affecting the dependent variables and which of the two has a stronger impact. Through these findings, we aim to draw conclusions to assist marketers in maximising their marketing efforts via sponsorship of blog advertorials.